Changes in Acute Poststreptococcal Glomerulonephritis: An Observation Study at a Single Korean Hospital Over Two Decades - Sueng-Woo Kuem; Sun-Mi Hur; You-Sook Youn; Jung-Woo Rhim; Jin-Soon Suh; Kyung-Yil Lee (Korean Society of Pediatric Nephrology, 2015)
Purpose: The incidence of acute poststreptococcal glomerulonephritis (APSGN) in Korea has changed. This study aimed to evaluate the epidemiological and clinical changes of APSGN observed in a single Korean institution over two decades. Methods: We retrospectively analyzed the data of 99 children (0-15 years of age) who were admitted to our institution with APSGN between 1987 and 2013. The patients were selected based on the depression of serum complement 3 (C3, <70 mg/dL) and elevated titer of antistreptolysin O (ASO, >250 IU/dL) as evidence of previous streptococcal infection. Results: In the 99 patients, the mean age was 8.3 ± 2.7 years, and the male-to-female ratio was 2.2:1 (66:30). The annual number of cases fluctuated markedly, and most cases were observed during the late autumn and winter months. However, there have been few cases reported in the past 5 years. Clinical manifestations at presentation, including hypertension and generalized oedema, and the duration of hospitalization were higher and longer in patients admitted during the first half of the study period than during the most recent half-period, suggesting a more severe clinical course in the former group. Conclusions: APSGN has become a rare disease in Korea with a trend towards a less severe clinical course. This finding suggests that the prevalence of infection-related immune-mediated diseases could change over-time, together with environmental and possibly pathogen-host relationship changes.